Hindan hoihpen : your best life now - Osteen, Joel (Lamka: Dr Mrs Dimjam Guite, 2020)
Counsels readers to draw on innate strengths in order to overcome obstacles, promote personal health, and live abundantly, in a guide that offers advice on acting in accordance with God's intentions rather than feelings.
Read by the author.
Keywords: Self-actualization (Psychology) -- Religious aspects -- Christianity; Success -- Religious aspects -- Christianity; Self-actualization (Psychology) -- Religious aspects -- Christianity; Success -- Religious aspects -- Christianity; Audiobooks; Audiobooks